Latent bacterial wilt and viral infection burden in the seed potato system in Ethiopia: Policy implications for seed potato - Tessema, L.; Kakuhenzire, R.; McEwan, M. (International Potato Center, 2023)
Executive Summary • The prevalence of infection with Ralstonia solanacearum (Rs) and viruses in seed potato systems is alarming, and continues to grow. • There is inadequate implementation of internal seed quality control and external quality assurance for early generation seed production (EGS). EGS materials being bulked were found to be infected by degenerative diseases, but there was limited awareness by seed producers of disease levels. • Most seed testing laboratories do not handle seed potato certification and those that do depend on visual assessment which is inadequate in ensuring seed health and increases the risk of spreading latent infections. • Most seed testing laboratories in Ethiopia suffer infrastructural, logistical, and human resource challenges that jeopardizes effective and efficient seed potato certification.